2018
DOI: 10.1016/j.visres.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Lag of accommodation does not predict changes in eye growth in chickens

Abstract: Emmetropization is controlled by the defocus in the retinal image. It is a classical problem how changes in focus, introduced by accommodation, are taken into account. We have quantified accommodation errors in chickens wearing negative lenses to find out whether they can predict subsequent eye growth. Two groups of chicks, aged 10 to 13 days, wore lenses (-7D) monocularly for 4-7 days. Fellow eyes remained untreated. Vitreous chamber depth (VCD) was measured in alert hand-held chickens with high resolution, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Finally, recent publications argue against a role of accommodation in emmetropization -accommodation appears to be largely ignored. [40][41][42][43] In summary, we believe that our results are not explained by differences in accommodation.…”
Section: Role Of Accommodationsupporting
confidence: 46%
“…Finally, recent publications argue against a role of accommodation in emmetropization -accommodation appears to be largely ignored. [40][41][42][43] In summary, we believe that our results are not explained by differences in accommodation.…”
Section: Role Of Accommodationsupporting
confidence: 46%
“…However, accommodative performance before lens treatment did not predict the amount of myopia induced, suggesting that the increased lag was a consequence of myopia, not a cause. Similarly, a recent study in chicks showed that accommodative lag does not predict the magnitude of lens‐induced myopia …”
Section: Accommodationmentioning
confidence: 95%
“…Similarly, a recent study in chicks showed that accommodative lag does not predict the magnitude of lens-induced myopia. 126 On the other hand, Diether and Wildsoet 127 investigated whether accommodation influenced the chick eye's ability to decode focusing errors and the relationship with spatial frequency and contrast. They found that when accommodation was eliminated through ciliary nerve section, decoding of, and compensation for, imposed defocus was impaired.…”
Section: Lens-induced Refractive Errorsmentioning
confidence: 99%
“…24 Axial lengths and vitreous chamber depths were measured in alert hand-held chickens, using a low coherence interferometer (Lenstar LS 900; Haag-Streit, Koeniz, Switzerland). 25 Measurements of Human Subfoveal Choroidal Area and Thickness. Subfoveal choroidal area was imaged with SD-OCT (HRAþOCT Spectralis), as previously described.…”
Section: Measurementsmentioning
confidence: 99%